(untitled) (Journal of Educational Management, 2000)
This study was designed to examine strategies needed for effective implementation of the Universal Basic Education in Nigeria. The population for the study was made up of all administrators of primary and secondary school systems in Delta State of Nigeria. The questionnaire was used for data collection,. and data analyses were converted into percentages. The findings revealed that the Government and administrators have important contributions towards effective implementation of the UBE. Fourteen strategies were identified for adoption by the Government while nine were identified for the administrators. Recommendations were based on the findings.